PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP KARAKTER KEAGAMAAN SISWA DI ERA DIGITAL - Zulham Zulham (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study is aims to anakyze the impact of social media usage on student’s religious character in the digital era. Rapid advancements in digital technology have transformed patterns of social interaction, particularly among children. A qualitative research approach was employed, utilizing data collection such as questionnaires, interviews, and observations. The findings indicate that social media usage has both positive and negative effects on student’s religious character. Positive impact are evident in the ease of maintaining social connections and accessing virtuos values. However negative impacts tend to be more pronounced in the absence of parental supervision, these include a decline in politeness (specifically regarding language etiquette), device addiction individualism, and exposure to content inconsistent with religious and social norms. Therefore, the active role of parent and early digital literacy are crucial in safeguarding children’s moral against the adverse effects of social media